Fluid intake is a strong predictor of outdoor team sport pre-season training performance - Badham, L.; Stern, S. E.; O`Connor, F. K.; Wijekulasuriya, G. A.; Corcoran, G.; Cox, G. R.; Coffey, V. G. (Journal of Sports Sciences, 2023)
Our aim was to characterize fluid intake during outdoor team sport training and use generalized additive models to quantify interactions with the environment and performance. Fluid intake, body mass (BM) and internal/external training load data were recorded for male rugby union (n = 19) and soccer (n = 19) athletes before/after field training sessions throughout an 11-week preseason (357 observations). Running performance (GPS) and environmental conditions were recorded each session and generalized additive models were applied in the analysis of data. Mean body mass loss throughout all training sessions was -1.11 ± 0.63 kg (~1.3%) compared with a mean fluid intake at each session of 958 ± 476 mL during the experimental period. For sessions >110 min, when fluid intake reached ~10-19 mL·kg-1 BM the total distance increased (7.47 to 8.06 km, 7.6%; P = 0.049). Fluid intake above ~10 mL·kg-1 BM was associated with a 4.1% increase in high-speed running distance (P < 0.0001). Most outdoor team sport athletes fail to match fluid loss during training, and fluid intake is a strong predictor of running performance. Improved hydration practices during training should be beneficial and we provide a practical ingestion range to promote improved exercise capacity in outdoor team sport training sessions.